Genre, Auteur and Identity in Contemporary Hollywood Cinema: Clint Eastwood’s White Hunter, Black Heart - García Mainar, Luis Miguel (Miscelánea: A Journal of English and American Studies, 2002)
The essay is an attempt firstly to look into the persistence of forms of auteurism in contemporary Hollywood cinema and, secondly, to prove the relevance of a joint genre-auteur analysis. Its starting point is the assumption that auteurs survive in, among other forms, the work of those directors who also act in their films, and whose film career has invested them with cultural connotations. Clint Eastwood is a case in point: his White Hunter, Black Heart (1990) illustrates how its generic configuration, as well as its representation of male identity, are inflected by the meanings associated with the auteur. The essay concludes that the complexity of meanings provided by the star-auteur lends the film an ambivalence that reveals its status as transition piece within the turmoil of gender and genre changes that affected the Hollywood cinema of the early 1990s.
Keywords: Authorship; Genre; Identity; Masculinity; Reflexivity